217k views
5 votes
See attachment to help

See attachment to help-example-1

2 Answers

4 votes
Multiply the first term in the left equation by all terms in the right equation. Then multiply the second term in the left equation by all terms in the right equation. Then combine all like terms. When multiplying exponents, you leave the base alone and add the exponents.

(f*g)(x) = (x^4-9)(x^3+9)
=(x^4*x^3)+(9*x^4)+(-9*x^3)+(-9*9)
=x^7+9x^4-9x^3-81

Hope this helps! :)
User Karlee
by
6.1k points
3 votes
(fg)(x) = (x^4 - 9)(x^3 + 9)
(fg)(x) = x^7 + 9x^4 - 9x^3 - 81

answer

(fg)(x) = x^7 + 9x^4 - 9x^3 - 81

User Simplylizz
by
5.7k points